Comparison of activation processes of activated carbon in removing pollutiants from palm oil mill effluents - Kaviraj, Anbarasan (2016)
Malaysia is the second leading exporter of palm oil in the world. In Malaysia and Indonesia, there are about 84% of world’s palm oil exports are produced. Indisputably, the level of our environment is affected by the oil palm industry and its processing and it may lead to the rise of ecological pollution. There are many types of treatment to improve POME quality and one of them is by using activated carbon. The purpose of this study is to compare two activation process of activated carbon in removing pollutants from palm oil mill effluent (POME). Samples were taken from Kilang Kelapa Sawit Lepar Hilir, Kuantan, Pahang Darul Makmur. The activated carbons were produced in two different method which are physical activation (pyrolysis treatment) and chemical activation (acidic treatment). The water quality parameters also were conducted based on the standard methods. Among the water quality parameters that involved are pH, BOD, COD, Ammoniacal Nitrogen, Turbidity, Oil & Grease, Total Suspended Solids and Heavy Metals (Boron, Copper and Lead). After analysing the wastewater quality based on eight parameters, both of samples showed the improvement in removing wastewater pollutant due to its removal efficiency. The results obtained are compared with the limits in the Environmental Quality Act 1984. Among the two samples, chemically activated carbon gave the most effective results due to its highest removal efficiency except in oil and grease parameter. The results of percentages of removal for wastewater treatment using chemically activated carbon for COD, BOD, TSS, AN, Turbidity and Oil & Grease are ranged from 98.99 to 99.68% while for physically activated carbon the results are between 97.69 to 99.63%. From the result obtained, it showed that activated carbon have potentials to be used as a filter medium in removing wastewater pollutant. This study had also lead to many recommendations in order to improve the potential of activated carbon as a wastewater pollutant removal.